Cardiovascular risk through anthropometric and biochemical indicators in patients of the psychiatric clinic of a reference hospital in Pará (Research, Society and Development, 2023)
This article aimed to assess cardiovascular risk in adult individuals with mental disorders admitted to a reference hospital. A descriptive, quantitative study was used in the methodology, with the sociodemographic, anthropometric, and clinical profile being investigated in the research. For data analysis, the G or Chi-square independence test was used followed by the Chi-square residual analysis to test the association between the different categories of a variable in two or more independent groups, the Student's t test was used to compare the biochemical variables at a significance level of 5% - p≤0.05. As a result, the population studied was predominantly female, incomplete primary education, out of the labor market, and living with their families. Most had a diagnosis of bipolar affective disorder, nutritional status of eutrophy and malnutrition, with risk for cardiovascular disease according to anthropometric indices. It is concluded from the study that individuals undergoing psychiatric treatment may present accumulation of adipose tissue in the abdominal region, classifying them with metabolic and cardiovascular risk, even with eutrophy or malnutrition. In addition to having low levels of HDL-c, which is related to dyslipidemia and risks to health and quality of life.